Assessing Student Satisfaction with Student Leaders' Performance - Maturan, John Carlo; Comandante, Mathena Pauline; Jabines, Nova Jane; Kolonas, Maria; Payosing, Hyacinth; Rosalejos, Ceikan; Galavia, Michel; Berdon, Lyka; Gulle, Reggienan; Guilalas, Joe Anne; Arpilleda, Alcher (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This study investigates the satisfaction levels of Grade 9 students at St. Paul University of Surigao regarding the performance of their student council. Recognizing the vital role that student leaders play in fostering a supportive educational environment, the research aims to assess key performance areas, including leadership skills, approachability, communication skills, and contributions to school activities. Utilizing a quantitative descriptive design, data were collected through a researcher-made questionnaire administered to a randomly selected sample of 134 students. The findings reveal that students express general satisfaction with their leaders (M=3.09, SD=0.61). Among the assessed variables, the highest satisfaction is noted in the area of contributions made by student leaders, which received a mean score of 3.20 (SD=0.57). This study highlights the importance of student councils as representative bodies that enhance student engagement and community involvement within educational institutions. By understanding student perceptions, the research provides valuable insights for current and future student leaders to improve their effectiveness and better meet the needs of their peers during the 2024-2025 academic year. Specifically, leaders may actively seek feedback from their peers through regular informal meetings or suggestion boxes, ensuring that all students feel comfortable voicing their concerns and ideas. Ultimately, fostering strong leadership within schools contributes to a more inclusive and enriching educational experience for all students.